Association of free Tri-iodothyronine Level with Cardiogenic Shock and Prognosis in Patients Hospitalized with Acute STelevation Myocardial Infarction Treated with Streptokinase Therapy - Huda, S M Nazmul; Choudhury, Amal Kumar; Jahan, Jafrin; Tabassum, Masuma; Rahman, Atikur; Debnath, Deb Dulal (Bangladesh Heart Journal, 2023)
Background: Cardiogenic shock is the leading cause of death in patients with Acute ST-segment Elevation Myocardial Infarction (STEMI). Low free Tri-iodothyronine (FT3) levels are generally associated with poor prognosis in STEMI patients. This study was done to assess the association between FT3 levels and Cardiogenic shock in patients hospitalized with STEMI treated with streptokinase therapy. Methods: This was an observational study of 140 patients of STEMI treated with streptokinase therapy in the department of cardiology, NICVD, Dhaka, Bangladesh from October 2018 to September 2019. The patients were divided into low FT3 (FT3 <3.5pmol/L; n = 70) and normal FT3 (FT3 e” 3.5pmol/L; n = 70) groups according to FT3 levels measured within 24 hours after admission. Results: During the index hospitalization period, 30 patients developed cardiogenic shock, 23(32.9%) in low FT3 group and 7(10.0%) in normal FT3 group. There were 17 deaths with 18.6% in low FT3 group and 5.7% in normal FT3 group (p=0.01). MACE occurred 45.7% in low FT3 group and 18.6%in normal FT3 group (p=0.001). The mortality in patients with cardiogenic shock was 43.3% compared to 3.6% in patients without cardiogenic shock. Multivariate logistic regression analysis showed FT3 level was an important predictor for cardiogenic shock in patients hospitalized with STEMI (p=0.01). Conclusion: Low FT3 levels were strongly associated with cardiogenic shock in patients with STEMI. The FT3 level screening may be a simple and valuable way to predict Cardiogenic shock after STEMI. Bangladesh Heart Journal 2023; 38(1): 1-7